From micellar electrokinetic chromatography to liquid chromatography‐mass spectrometry: Revisiting the way of analyzing human fluids for the search of desmosines, putative biomarkers of chronic obstructive pulmonary disease. Issue 1 (23rd October 2013) - Viglio, Simona; Stolk, Jan; Luisetti, Maurizio; Ferrari, Fabio; Piccinini, Paolo; Iadarola, Paolo; El, Ziad
<x xml:space="preserve">Abstract</x> Desmosine (DES) and isodesmosine are two isomer amino acids unique‐to‐mature, cross‐linked elastin. Based on this feature, they have been discussed as surrogate markers of chronic obstructive pulmonary disease, a disorder characterized by progressive degradation of lung elastin. Despite the development of numerous protocols, detection of DESs in body fluids is still considered to be technically challenging. In fact, owing to the minute concentration of these circulating cross‐links, their accurate measurement may be provided only by sophisticated and sensitive techniques. Aim of this article is to present the "history" of the two techniques (MEKC and LC‐MS) that, better than others, allowed scientists to "bring their best to the table" in this area. Both of them meet the criteria of (almost) complete automation of the procedure and of the use of more selective and sensitive detection systems. The substantial advantages in terms of precision and accuracy provided by such measurements suggest that the science of DESs is eventually catching up with its promise and the assumption that these candidate biomarkers can be associated to clinical variables holds true.